Optimization of FSW parameters for maximum UTS of AA6082/SiC/10P composites. (4th September 2019) - Bhushan, Rajesh Kumar; Sharma, Deepak
Friction stir welding (FSW) offers significant advantage when compared with fusion joining process such as no shield gas or flux are used, no harmful gases are produced, thereby making the FSW environmentally friendly. In this work, an experimental approach has been used for studying and optimizing the FSW process, applied on AA6082/SiC/10P composite plates. In particular, the effect of process parameters on ultimate tensile strength (UTS) of FSW joint has been investigated. The UTS of FSW joints is affected by FSW parameters. The FSW of the AA6082/SiC/10P composite plates was carried out with different combinations of FSW parameters. The experiments were conducted according to the Taguchi's L9 orthogonal array. Taguchi method of designing the experiments was used for optimization of the FSW parameters. The signal to noise ratio and analysis of variance were used to determine the effects of FSW parameters on the UTS of the welded joints. The optimum FSW parameters for the maximum UTS were found to be the tool rotation speed of 1800 r/min, the welding speed of 100 mm/min and the tool tilt angle of 2°. UTS increased by 24.5% when FSW was carried out at optimum process parameters as compared to initial FSW parameters. Results have shown good agreement between the predicted and experimental values of UTS. High tensile strength is required for use of FSWed AA6082/SiC/10P composite joints in aerospace industry.